The diagnosis dilemma of coexistence of neurosarcoidosis and tuberculosis: case reports and literature review - Sun, Qing; Jiao, Jinsong; Wang, Renbin; Wu, Dongyan; Dai, Huaping; Shu, Shi; Su, Yunchao; Peng, Dantao; Zhang, Weihe; Duan, Xiaohui (Frontiers in Medicine, 2026)
Sarcoidosis is a multisystem disease pathologically characterized by non-caseating epithelioid granulomas. Its neurological form, neurosarcoidosis (NS), can affect the central nervous system (CNS) and/or the peripheral nervous system (PNS), posing a significant diagnostic challenge. The diagnostic dilemma is further complicated by the significant clinicopathological overlap between sarcoidosis and tuberculosis (TB). Although rare, sarcoidosis and TB can coexist. Our case series included three NS patients: two had CNS involvement and one had PNS involvement. Notably, two patients had confirmed active tuberculosis infection and one patient had a latent TB infection. This highlights the diagnostic and therapeutic challenges of these coexisting conditions. Fluorodeoxyglucose positron emission computed tomography (FDG PET) helps detect extraneural sarcoidosis locations and find biopsy sites. Regarding the similarity and potential coexistence of TB and sarcoidosis, thorough screening for TB infection is essential before initiating any therapy for sarcoidosis.